Costs, affordability, and feasibility of an essential package of cancer control interventions in low-income and middle-income countries: key messages from Disease Control Priorities, 3rd edition. Issue 10033 (21st May 2016) - Gelband, Hellen; Sankaranarayanan, Rengaswamy; Gauvreau, Cindy L; Horton, Susan; Anderson, Benjamin O; Bray, Freddie; Cleary, James; Dare, Anna J; Denny, Lynette; Gospodarowicz, Mary K; Gupta, Sumit; Howard, Scott C; et al.
Summary: Investments in cancer control—prevention, detection, diagnosis, surgery, other treatment, and palliative care—are increasingly needed in low-income and particularly in middle-income countries, where most of the world's cancer deaths occur without treatment or palliation. To help countries expand locally appropriate services, Cancer (the third volume of nine in Disease Control Priorities, 3rd edition) developed an essential package of potentially cost-effective measures for countries to consider and adapt. Interventions included in the package are: prevention of tobacco-related cancer and virus-related liver and cervical cancers; diagnosis and treatment of early breast cancer, cervical cancer, and selected childhood cancers; and widespread availability of palliative care, including opioids. These interventions would cost an additional US$20 billion per year worldwide, constituting 3% of total public spending on health in low-income and middle-income countries. With implementation of an appropriately tailored package, most countries could substantially reduce suffering and premature death from cancer before 2030, with even greater improvements in later decades.